QUALITATIVE AND QUANTITATIVE ANALYSIS OF HYDROQUINONE CONTENT IN MARKETPLACE FACIAL WHITENING CREAMS - Zaman Ruchiyat; Nanda Raudhatil Jannah; Ayu Shalihat (FKIP USK, 2023)
Hydroquinone is one of the dangerous ingredients in facial whitening cream cosmetics which can cause skin irritation, skin redness and a burning feeling. The purpose of this study was to determine the hydroquinone content in facial whitening cream cosmetics sold in the marketplace. The method used in this study was a qualitative test using a colour reagent test and the Thin Layer Chromatography (TLC) method with toluene:glacial acetic acid as the mobile phase (5:5) and Silica Gel254 Plate as the stationary phase. Quantitative analysis used the UV Vis spectrophotometry method at a wavelength of 541 nm. The results of the qualitative test in the TLC test showed that 4 samples tested positive for hydroquinone in samples A, B, D, and E, with a range of Rf values of 0.44, 0.5, 0.52, and 0.5, respectively. The results of the quantitative test showed that 9 samples contained hydroquinone with a sample content range of 0.22 to 3.62 ppm with an LoD value of 0.637 ppm and an LoQ of 2.124 ppm. The results of this study indicate that there are still cosmetics containing hydroquinone, these results are not following the Regulation of Badan Pengawas Obat dan Makanan (BPOM) No. KH. 00.01.43.2503 of 2009 where the use of this hydroquinone ingredient is prohibited for use in facial whitening creams because it can endanger health.Keywords: Analysis, Hydroquinone, TLC, Whitening Cream